2015
DOI: 10.1111/phn.12219
|View full text |Cite
|
Sign up to set email alerts
|

Decision Tree Identified Risk Groups with High Suicidal Ideation in South Korea: A Population‐Based Study

Abstract: Public health nurses and community mental health professionals should recognize risk groups with high suicidal ideation, and target these groups when implementing preventive interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Within the domain of mental health, recent studies using decision trees have primarily examined associations with depression [14][15][16][17][18][19] and suicide risk. 15,[20][21][22][23][24][25][26][27][28] Two studies examined depression outcomes in youth populations specifically. Hill et al 16 found that, among students with subclinical depressive symptoms at baseline, friend support was protective against developing major depressive disorder by age 30, with anxiety disorder and substance use disorder increasing risk among those without friend support.…”
Section: Introductionmentioning
confidence: 99%
“…Within the domain of mental health, recent studies using decision trees have primarily examined associations with depression [14][15][16][17][18][19] and suicide risk. 15,[20][21][22][23][24][25][26][27][28] Two studies examined depression outcomes in youth populations specifically. Hill et al 16 found that, among students with subclinical depressive symptoms at baseline, friend support was protective against developing major depressive disorder by age 30, with anxiety disorder and substance use disorder increasing risk among those without friend support.…”
Section: Introductionmentioning
confidence: 99%
“…These tools enable the automatic identification of patterns and similarities, facilitating the interpretation of large data volumes. 14 Kim et al 14 explain that, based on the analysis of the relationships between risk factors, the DT can predict groups that are at higher risk of developing a certain outcome. In addition, the tree format facilitates the understanding of how these relationships culminate in the risk levels.…”
Section: Introductionmentioning
confidence: 99%
“…Decision trees (DTs) can be used to overcome this difficulty. These tools enable the automatic identification of patterns and similarities, facilitating the interpretation of large data volumes 14 . Kim et al 14 .…”
Section: Introductionmentioning
confidence: 99%
“…In the existing literature, the focus has predominantly converged on the repercussions of widowhood on mental health dimensions, such as depressive manifestations or suicidal tendencies in the older adults (14,21,22). Yet, a discernible research void persists regarding widowhood's bearing on facets like family support.…”
Section: Introductionmentioning
confidence: 99%